2010
DOI: 10.1097/sla.0b013e3181c5ddc3
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of the Presence of Concomitant Invasive Ductal Carcinoma in Intraductal Papillary Mucinous Neoplasm of the Pancreas

Abstract: In view of the high prevalence of DC careful inspection of the entire pancreatic gland is necessary for early detection of DC in patients with branch duct IPMNs, especially when worsening diabetes mellitus and an abnormal serum CA 19-9 level are manifested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(85 citation statements)
references
References 26 publications
3
79
1
2
Order By: Relevance
“…Additionally, there have been some retrospective studies of PC concomitant with IPMN (Table 2). 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30 These studies demonstrated that the frequency of PC concomitant with IPMN ranged from 1.1% to 11.2%. As for branch duct IPMN, two working groups of JPS reported that seven PC cases were detected in 349 branch duct IPMN cases during the follow‐up period,17 and that PC concomitant with IPMN may be diagnosed earlier than ordinary PC 18.…”
Section: Risk Factors and Early Diagnosismentioning
confidence: 85%
“…Additionally, there have been some retrospective studies of PC concomitant with IPMN (Table 2). 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30 These studies demonstrated that the frequency of PC concomitant with IPMN ranged from 1.1% to 11.2%. As for branch duct IPMN, two working groups of JPS reported that seven PC cases were detected in 349 branch duct IPMN cases during the follow‐up period,17 and that PC concomitant with IPMN may be diagnosed earlier than ordinary PC 18.…”
Section: Risk Factors and Early Diagnosismentioning
confidence: 85%
“…The same authors reported 76 patients who underwent resection of BD-IPMN, of which 7 (9.2%) had concomitant noninvasive or invasive pancreatic cancer [52]. Subsequent reports of cases [53,54] and many series from Japan [55,56,57,58,59,60,61,62] indicate that concomitant pancreatic cancer occurs in 2-10% of patients with IPMN [63]. Even a small (≤1 cm diameter) BD-IPMN is associated with an 8% risk of developing distinct pancreatic cancer during surveillance [56].…”
Section: Invasive Pancreatic Cancer Concomitant With Ipmnmentioning
confidence: 99%
“…These figures are perplexing, especially if we keep in mind that some 10% of individuals older than 70 years have a sub-centimeter pancreatic cyst. Our own experience and reports by other groups lead us to believe that this seemingly high prevalence of HGD and invasive carcinoma arising from very small BD-IPMN could be explained by the presence of a small IPMN with LGD adjacent to a concomitant conventional PDAC, as the distinction between the two events is often challenging [10,74,75].…”
Section: Iap and Aga Guidelines: How We Use Themmentioning
confidence: 99%
“…There is no conclusive evidence that multifocal IPMN pose a higher risk of HGD or invasive carcinoma, and we thus recommend that each cyst be assessed individually, rather than performing a total pancreatectomy upfront [10,48,72]. More critically, concomitant PDAC may develop in 3-11% of patients, either in the primary resection specimen or as a metachronous event [73][74][75]. While our experience suggests that metachronous PDAC after resection for IPMN is uncommon (0.5%), other series have reported a 5-and 10-year cumulative incidence of 4.5 and 5.9%, respectively [76].…”
Section: Follow-up Of Resected Patients: Predicting Recurrent and Newmentioning
confidence: 99%